Comprehensive medicinal chemistry II - Taylor, J. B. (John Bodenhan), 1939-; Triggle, D. J. (Elsevier, 2007)
This e-book comprises 8 volumes, with all chapter sections available as PDF or HTML, and includes bibliographical references and index.